Association between insurance status, anticoagulation quality, and clinical outcomes in patients with acute venous thromboembolism. Issue 173 (January 2019) - Zumbrunn, Brigitta; Stalder, Odile; Méan, Marie; Limacher, Andreas; Tritschler, Tobias; Rodondi, Nicolas; Aujesky, Drahomir
Abstract: Introduction: A higher level of health insurance coverage may be related to better quality of care and outcomes. Whether insurance status is associated with anticoagulation quality and clinical outcomes in patients with venous thromboembolism (VTE) is unknown. Methods: We studied 819 elderly patients treated with vitamin K antagonists for VTE in a Swiss prospective multicenter cohort (09/2009–12/2013). The study outcomes were the anticoagulation quality, defined as the time spent in the therapeutic INR range, and clinical events, i.e. the time to a first VTE recurrence, major bleeding, and mortality. We assessed the association between insurance status (private vs. general), anticoagulation quality, and clinical outcomes using regression models, adjusting for potential confounders. Results: Although the unadjusted mean percentage of time spent in the therapeutic INR range (2.0–3.0) was slightly higher in patients with private vs. general insurance (65% vs. 61%; p = 0.030), the adjusted difference was not statistically significant (1.53%, 95% CI −1.97 to 5.04). Patients with private insurance had a lower 36-month cumulative incidence of major bleeding (9.7% vs. 15.7%; p = 0.018). After adjustment, privately insured patients had a lower risk of major bleeding compared to patients with general insurance (sub-hazard ratio 0.57, 95% CI 0.32 to 0.98). Insurance status was not associated with recurrent VTE or mortality. Conclusion: Privately insured patients spent somewhat more time in therapeutic INR range and had a lower rate of major bleeding than generally insured patients. Basic (general) health insurance may be a marker of lower anticoagulation quality and higher risk of major bleeding. Highlights: The level of health insurance may affect anticoagulation and clinical outcomes. Patients with private health insurance spent more time in the therapeutic INR range. Private insurance was associated with a lower risk of major bleeding. Insurance status was not associated with recurrent venous thromboembolism or mortality.